DETERMINASI KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - NISA, USWATUN (Jurnal Akuntansi AKUNESA, 2019)
This study aims to examine the effect of profitability, cash flow, firm size, liquidity, leverage, investment opportunity, and corporate tax on dividend policy. The sample in this study were manufacture companies from the BEI for the period 2012-2017. The sample were selected using purposive sampling technique and obtained a sample of 35 companies. The analysis technique used in this study is multiple linear regressions analysis using IBM SPSS Statistic program 23. The results of the study show that profitability and corporate tax has a positive effect on dividend policy. Then, cash flow, firm size, liquidity, leverage, and investment opportunity has no effect on dividend policy.